Segmental Analysis of Chlorprothixene and Desmethylchlorprothixene in Postmortem Hair. Issue 9 (26th June 2018) - Günther, Kamilla Nyborg; Johansen, Sys Stybe; Wicktor, Petra; Banner, Jytte; Linnet, Kristian
Abstract: Analysis of drugs in hair differs from their analysis in other tissues due to the extended detection window, as well as the opportunity that segmental hair analysis offers for the detection of changes in drug intake over time. The antipsychotic drug chlorprothixene is widely used, but few reports exist on chlorprothixene concentrations in hair. In this study, we analyzed hair segments from 20 deceased psychiatric patients who had undergone chronic chlorprothixene treatment, and we report hair concentrations of chlorprothixene and its metabolite desmethylchlorprothixene. Three to six 1-cm long segments were analyzed per individual, corresponding to 3–6 months of hair growth before death, depending on the length of the hair. We used a previously published and fully validated liquid chromatography-tandem mass spectrometry method for the hair analysis. The 10th–90th percentiles of chlorprothixene and desmethylchlorprothixene concentrations in all hair segments were 0.05–0.84 ng/mg and 0.06–0.89 ng/mg, respectively, with medians of 0.21 and 0.24 ng/mg, and means of 0.38 and 0.43 ng/mg. The estimated daily dosages ranged from 28 mg/day to 417 mg/day. We found a significant positive correlation between the concentration in hair and the estimated daily doses for both chlorprothixene ( P = 0.0016, slope = 0.0044 [ng/mg hair]/[mg/day]) and the metabolite desmethylchlorprothixene ( P = 0.0074). Concentrations generally decreased throughout the hair shaft from proximal to distal segments, with an average reduction in concentration from segment 1 to segment 3 of 24% for all cases, indicating that most of the individuals had been compliant with their treatment. We have provided some guidance regarding reference levels for chlorprothixene and desmethylchlorprothixene concentrations in hair from patients undergoing long-term chlorprothixene treatment.